USING ONLINE LEARNING DURING THE COVID-19 PANDEMIC AT JUNIOR HIGH SCHOOL IN PADANG PARIAMAN - Wahyu Ardila; Suharni Suharni; Herfyna Asty (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
The purpose of this study is to find out the implementation of online learning used by English teachers at SMP Negeri Padang Pariaman Regency during the COVID-19 pandemic. The data collection techniques used in this research were questionnaires. The technique of Data Analysis was a data processing technique that aims to obtain the right conclusions. In this researcher used data analysis techniques qualitative using a survey design. The researcher found the implementation of online learning has been carried out well, starting from learning planning, implementing learning/learning process, and learning evaluation. In learning planning has been carried out well, because the average answer of teachers who choose answers is agree and strongly agree in learning planning. In learning process has been carried out well, because the average answer of teachers who choose answers is agree, strongly agree and only a few teachers disagree with implementing the online learning process. In learning evaluation has been carried out well, because the average answer of teachers who choose answers is agree, strongly agree and only a few teachers disagree with implementing the online learning evaluation.